Museum Staff: Defining Expectations. - Emery, Alan R. (Museum Management & Curatorship)
The article provides information on the conceptual framework model for any museum. It notes the organizational chart which serves as a model of the hierarchic reporting relationships of the persons within an organization. It also mentions the three assumptions formed by the model including various people on staff, one person in charge, and board of trustees.